2011
DOI: 10.1039/c1cs15162b
|View full text |Cite
|
Sign up to set email alerts
|

Engineering DNA-based functional materials

Abstract: While DNA is a genetic material, it is also an inherently polymeric material made from repeating units called nucleotides. Although DNA's biological functions have been studied for decades, the polymeric features of DNA have not been extensively exploited until recently. In this tutorial review, we focus on two aspects of using DNA as a polymeric material: (1) the engineering methods, and (2) the potential real-world applications. More specifically, various strategies for constructing DNA-based building blocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
191
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(192 citation statements)
references
References 82 publications
0
191
0
1
Order By: Relevance
“…We foresee that a large variety of topics in statistical physics can be experimentally addressed through the use of DNA supermolecules, including reentrant behaviors induced by competitive interactions (34,35), higher-order network-network critical points (36), and arrested states of matter (glasses and gels) (27). In the specific case of limited valence structures here discussed, our results set the basis to predict the thermal and kinetic stability of self-assembled DNA hydrogels (25), a finding with relevant implications in the design of commercial complex fluids with tailored properties. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We foresee that a large variety of topics in statistical physics can be experimentally addressed through the use of DNA supermolecules, including reentrant behaviors induced by competitive interactions (34,35), higher-order network-network critical points (36), and arrested states of matter (glasses and gels) (27). In the specific case of limited valence structures here discussed, our results set the basis to predict the thermal and kinetic stability of self-assembled DNA hydrogels (25), a finding with relevant implications in the design of commercial complex fluids with tailored properties. …”
mentioning
confidence: 99%
“…Because the binding between sticky overhangs is stronger than all other interparticle interactions (excluded volume, van der Waals, electrostatic), DNA nanostars provide an optimal model for highlighting the role of the valence. Similar DNA nanostars were studied by Luo and coworkers (24,25) to investigate their gelation in the presence of enzymatic catalysis. We operate in the absence of any enzymes to benefit the reversibility of the DNA interaction and systematically investigate the equilibrium phase behavior.…”
mentioning
confidence: 99%
“…Hence, the cytoskeleton of liposomes should be constructed with defined and designable materials. To accomplish this aim, DNA nanotechnology, which uses limited components with high designability in a nanometer scale (11), is a feasible candidate to construct cytoskeleton structures in artificial cells.…”
mentioning
confidence: 99%
“…Exploiting the specificity of Watson-Crick base pairing has produced complex dynamic structures such as molecular computers,(1) motors,(2) nanoreactors,(3) as well as sensors and diagnostics. (4)(5)(6)(7)(8)(9)(10) More recently, the ability of certain drugs to intercalate within the DNA double helix and form strong physical complexes has been utilized to form physical prodrugs for cytotoxics. Farokhzad et al first demonstrated that a DNA aptamer could be loaded with doxorubicin (DOX), allowing targeted uptake into cells presenting the aptamer target.…”
Section: Introductionmentioning
confidence: 99%